Presence of Arbuscular Mycorrhizal Fungi in Coastal Forest Based on The Salinity Gradients - D Delvian (Jurnal ILMU DASAR, 2010)
The role of arbuscular mycorrhizal fungi is very important in a coastal area with sandy soil, high salinity level and low available of phosphate. However, the salinity levels also affect the diversity and activities of mycorrhizal fungi. This research was aimed to learn about arbuscular mycorrhizal fungi in coastal forest based on the salinity gradients. The results demonstrated that spore density and percentage of mycorrhizal colonization decreased by increasing the soil salinity. The same effect was also showed on the observed spore types. Glomus was found as the dominant spore in the research area.